Development of a reference grid performance assessment model an alternative regulatory framework for the transmission company in a market environment - Calibjo, Cirilo C.
A new regulatory model based on reference networks is being proposed for the transmission company in a market environment. Applying a novel non-dominated sorting differential evolutionary algorithm (NSDEA) to a DC power flow based multi-objective transmission expansion planning (MOTEP) model, this paper aims to develop a Reference Grid Performance Assessment Model that can be used as a benchmark when evaluating investment proposals for the transmission upgrade. Investment cost, line rental cost and amount of load curtailment are considered in the optimization as the three objective prerequisites. In addition, the static MOTEP problem has been investigated in both greenfield and expansion planning problem with and without generation rescheduling considerations. The proposed model was applied to Garvers 6-bus system, the IEEE 25-bus test system, a realistic South Brazilian system and the reduced Luzon grid of the Philippines. Simulation results of the different test systems show the accuracy, outstanding convergence performance in finding the optimal solution, simple implementation as well as satisfactory computation time of the proposed solution technique.